Hubungan Antara Pet Attachment Dengan Psycological Well Being Pada pemilik Hewan Peliharaan - Paduli, Gretha; Sumoked, Chelshea (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to examine the relationship between Pet Attachment and Psychological Well-Being in pet owners. Attachment to pets is considered to have a positive impact on the mental health of their owners. This study uses a quantitative method with an instrument in the form of a questionnaire distributed to a number of pet owner respondents. The results of the data analysis show that there is a significant and positive relationship between Pet Attachment and Psychological Well-Being, with a correlation coefficient of 0.805. This indicates that the stronger the owner's attachment to their pet, the higher the psychological well-being felt by the owner. This study suggests that further studies be conducted by including moderator variables such as gender, age, length of pet ownership, and social support from family and friends. In addition, further research can use more diverse methods, such as longitudinal studies and in-depth interviews, to gain a more comprehensive understanding of the long-term impact of Pet Attachment on psychological well-being. This study also has theoretical implications that enrich the literature related to human-animal interactions and their contribution to mental health. Limitations of the study include the use of limited variables and the short study time, which need to be considered in future studies.